Profile of Intensive Care Unit admission and Outcomes of Medical and Surgical patients at A Tertiary Government Hospital: A 5 Year Trend Analysis (Bangladesh Journal of Medicine, 2018)
Background: The intensive care unit (ICU) is that part of the hospital where critically ill patients that require advanced airway, respiratory and haemodynamic supports are usually admitted. Intensive care unit admissions which aim at achieving an outcome better than if the patients were admitted into other parts of the hospital however come at a huge cost to the hospital, the personnel and patients’ relations.Objective: To audit the 5 year bed occupancy rate and outcome of medicine and surgical patients admitted into the ICU of the Chittagong Medical College Hospital, Chittagong, Bangladesh.Design: A 5 years retrospective study (Record review) from January 2012 to December 2016. Method: Data were extracted from the ICU records of the patient and analyzed.Results: During this study period, the frequency of admission into ICU was significantly more (p